2018
DOI: 10.17236/sat00179
|View full text |Cite
|
Sign up to set email alerts
|

Defining daily doses and total doses for the measurement of antibiotic usage in Swiss pig production

Abstract: A significant Antibiotic-Monitoring-System is essential to analyse the use of antibiotics and to a better understanding of trends in resistance development. In human and veterinary medicine, for example, a system based on defined daily and treatment doses (Defined Daily Dose: DDD and Defined Course Dose: DCD) is applied. These definitions can be used to estimate the number of treatment days and treatments with antimicrobial agents in a population. For veterinary medicine, the European Medicines Agency (EMA) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…For example, macrolides showed a difference in calculated use depending on whether Swiss or European definitions were chosen. As a previous study showed, there are six Swiss premix products containing the macrolide tylosin with much lower defined daily and course doses compared to the values of the EMA (20), thus explaining the relatively high number of DDDch and DCDch in this category. This general understanding can also be used to explain the results in Table 1.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, macrolides showed a difference in calculated use depending on whether Swiss or European definitions were chosen. As a previous study showed, there are six Swiss premix products containing the macrolide tylosin with much lower defined daily and course doses compared to the values of the EMA (20), thus explaining the relatively high number of DDDch and DCDch in this category. This general understanding can also be used to explain the results in Table 1.…”
Section: Discussionmentioning
confidence: 92%
“…These values were defined by calculating the mean of given registrations for livestock production from nine different European countries. In analogy with the principles of the EMA (19), national defined doses (DDDch and DCDch) for each individual registration in the pig sector in Switzerland were recently determined and some theoretically discrepancies between Swiss and European values have been described in a prior study (20).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, national DDDs and DCDs have been developed in several countries (15,22,23). For this reason, separate Defined Daily Doses (DDDch) and Defined Course Doses (DCDch) were developed for Switzerland, some of which consequently showed considerable deviations from the indicators published by the EMA (21,(23)(24)(25)(26). Due to these discrepancies, some authors consider the so-called treatment incidence based on used daily doses, which describes the proportion of treated animals at Abbreviations: AMU, antimicrobial usage; AS, active substance; ATI, Animal Treatment Index; DDDch, Defined Daily Dose Switzerland; DCDch, Defined Course Dose Switzerland; DDDvet, Defined Daily Dose (EMA); DCDvet, Defined Course Dose (EMA); EMA, European Medicines Agency; Min, minimum; Max, maximum; NT, number of treatment days; nDDDch, number of DDDch; SD, standard deviation; SW, standard weight; VMP, Veterinary Medical Product.…”
Section: Introductionmentioning
confidence: 99%
“…The DDDvet values based on data from nine European countries have been shown in some cases to differ considerably from the dosages specified in the respective national summaries of product characteristics (SPCs). Therefore, national DDDs and DCDs have been developed in several countries ( 15 , 22 , 23 ). For this reason, separate Defined Daily Doses (DDDch) and Defined Course Doses (DCDch) were developed for Switzerland, some of which consequently showed considerable deviations from the indicators published by the EMA ( 21 , 23 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation